2008
DOI: 10.1073/pnas.0803945105
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the inflammatory response in stroke in vivo by sensing the enzyme myeloperoxidase

Abstract: Inflammation can extend ischemic brain injury and adversely affect outcome in experimental animal models. A key difficulty in translating animal studies to humans is the lack of a definitive method to confirm and track inflammation in the brain in vivo. Myeloperoxidase (MPO), a key inflammatory enzyme secreted by activated neutrophils and macrophages/microglia, can generate highly reactive oxygen species to cause additional damage in cerebral ischemia. We report here that a functional, enzyme-activatable MRI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
241
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(261 citation statements)
references
References 33 publications
15
241
2
3
Order By: Relevance
“…Our in vitro studies of myeloid cells coincubated with HUVECs indicate that G-CSFtreated myeloid cells are angiotoxic to E-selectin-expressing endothelial cells; this effect is ameliorated by interruption of E-selectin receptor/ligand interactions and by inhibition of MPO activity. Although further studies are necessary to directly assess the role(s) of MPO-EL in vasculopathy, these findings offer novel perspectives on the association between MPO expression and vascular injury: in vivo, MPO-EL could serve as a key effector of sickle cell crises (28), myocardial infarction and coronary artery disease (29,30), atherosclerosis (31,32), and stroke (33), conditions which have all been linked to MPO. Indeed, G-CSF administration can trigger angina and myocardial infarction (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro studies of myeloid cells coincubated with HUVECs indicate that G-CSFtreated myeloid cells are angiotoxic to E-selectin-expressing endothelial cells; this effect is ameliorated by interruption of E-selectin receptor/ligand interactions and by inhibition of MPO activity. Although further studies are necessary to directly assess the role(s) of MPO-EL in vasculopathy, these findings offer novel perspectives on the association between MPO expression and vascular injury: in vivo, MPO-EL could serve as a key effector of sickle cell crises (28), myocardial infarction and coronary artery disease (29,30), atherosclerosis (31,32), and stroke (33), conditions which have all been linked to MPO. Indeed, G-CSF administration can trigger angina and myocardial infarction (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies suggest that unlike MPO, eosinophil peroxidase is inefficient in oxidizing, and hence 'activating' MPO-Gd [162]. Moreover, in vivo studies employing MPO-deficient mice and models of MI and stroke showed no agent activation [160,163], indicating that MPO-Gd is a relatively specific imaging agent for assessment of MPO activity. Furthermore, MPO-Gd is highly sensitive and able to detect MPO concentrations as low as 0.005 U/mg, which is substantially lower than levels present in many pathological conditions (e.g.…”
Section: Mri Of Mpo Activity With Bis-5ht-dtpagadoliniummentioning
confidence: 99%
“…Рекрутирование циркулирующих моноцитов в зону инфаркта и пенумбры в модели инсульта происходит через 24 часа после окклюзии арте-рии, и моноциты детектируются в зоне повреж-дения в течение 14 дней с пиком на 3-7 сутки [11]. Первоначально считалось, что рекрутируемые моноциты/макрофаги усиливают ишемическое повреждение и способствуют прогрессии вто-ричных повреждений [26].…”
Section: продукция провоспалительных медиаторовunclassified